2020
DOI: 10.1080/23818107.2019.1703808
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological variation in Chara contraria and a taxon morphologically resembling Chara connivens

Abstract: mainly interested in ecology of aquatic macrophytes, particularly in charophyte algae ecology. Contribution: field work, manuscript writing.Jelena Blazenčić is a retired full-time professor at the University of Belgrade, Faculty of Biology, with a long and fruitful career devoted to charophyte research, prevalently in Balkan Peninsula. Her bibliography confirms her as one of the leading experts in the field of charophytes research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Urbaniak and Gąbka [ 6 ] remarked the irregularity of the cortex, which was also noted in this study. It was already shown that the number of cortex cell rows may be variable within a genetically homogeneous Chara group [ 22 ], which may be the case in C. baueri as well.…”
Section: Discussionmentioning
confidence: 99%
“…Urbaniak and Gąbka [ 6 ] remarked the irregularity of the cortex, which was also noted in this study. It was already shown that the number of cortex cell rows may be variable within a genetically homogeneous Chara group [ 22 ], which may be the case in C. baueri as well.…”
Section: Discussionmentioning
confidence: 99%
“…An exception is a case of Sava Lake, where in a recent study, only one previously detected species was reconfirmed-C. contraria, while Tolypella intricata and Nitella sp. are newly recorded [91]. Findings in Sava Lake and a nearby small lake Ada Safari [87,91] are at least intriguing, considering high anthropogenic pressure on this recreational center.…”
Section: Macroalgae In Vojvodinamentioning
confidence: 98%
“…In terms of species ecology, the Slatina locality could be considered the only one typical for C. connivens in Serbia. Specimens found in the explicitly freshwater Dulin pond turned out to be genetically specific (Trbojević et al 2020) Dicranum polysetum is a calcifuge species which usually grows on the ground in forests and plantations, especially under pines and birches, in boreal and continental climates (Blockeel et al 2014). This circumpolar boreal-montane species is widespread in North, Central and Eastern Europe.…”
Section: Chara Connivensmentioning
confidence: 99%
“…Blaženčić 30.09.1983 and17.07.1984). However, in June 2017, it was discovered at the new site of Dulin pond, a shallow, permanent freshwater body, situated in the Deliblato Sands Nature Reserve (Trbojević et al 2020). The finding in Slatina, near Baranda, is hence the third record for Serbia.…”
mentioning
confidence: 99%